Chrystianizacja i romanizacja elit w rzymskiej Edessie - Jędrzejewska, Daria (Vox Patrum, 2020)
In the pre-Roman history of Edessa and Osrhoene, the role of the local elites, gathered around the royal court, was clearly visible. By this time, Edessean upper classes were strongly influenced with Iranian culture. In the process of incorporation of Osrhoene into Roman Empire, the elites of Edessa took over some Roman cultural models, and their representatives participated in the local administration already after the fall of the Abgarid dynasty in 242 BC. This article aims to trace in sources concerning the history of Edessa references to the local aristocracy. Apparently this group continued to play a role after the transformation of the kingdom into a province, but remained in the shadow of dynamically developing ascetic Syrian Christianity. The elites of Edessa are associated with the figure of Bar Daisan, whose teachings and sect called the Bardezanites survived at least until the fifth century; probably the same circles preserved and modelled the record of conversion of the King of Edessa (S. Brock's theory), which was generally accepted by the inhabitants of the city. Although the sources mention the elites of Edessa occasionally and reluctantly, the most important tradition associated with them - the legend of the conversion of the city - became the factor that made Edessa famous in the Roman world.